2014
DOI: 10.1007/s10562-014-1468-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Ammonia by Co-adsorbed Oxygen on Iridium Surfaces: Formation of N2O

Abstract: Temperature programmed desorption is used to investigate ammonia oxidation by pre-adsorbed oxygen on planar Ir(210) and faceted Ir(210) with different facet sizes. Evidence is found for formation of N 2 O from both surfaces, which is the first observation of N 2 O production in catalytic ammonia oxidation under UHV conditions (\1 9 10 -9 Torr). The selectivity of the reaction to N 2 , N 2 O and NO can be tuned by oxygen pre-coverage, surface structure, and facet size. The reaction exhibits strong structure sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…The nitrogen selectivity increases with the adsorption of NO x and N 2 O x species, as the oxidation of NH 3 is inhibited due to the reduced concentration of surface-active O. These results are consistent with studies on Ir-based and Au-based catalysts. Karatok et al reported that disordered surface atomic O can selectively catalyze N–H bond cleavage, yielding mainly N 2 products, while the O/Ag(111) surface with higher oxygen coverage shows higher selectivity for N 2 O than N 2 .…”
Section: Introductionsupporting
confidence: 89%
“…The nitrogen selectivity increases with the adsorption of NO x and N 2 O x species, as the oxidation of NH 3 is inhibited due to the reduced concentration of surface-active O. These results are consistent with studies on Ir-based and Au-based catalysts. Karatok et al reported that disordered surface atomic O can selectively catalyze N–H bond cleavage, yielding mainly N 2 products, while the O/Ag(111) surface with higher oxygen coverage shows higher selectivity for N 2 O than N 2 .…”
Section: Introductionsupporting
confidence: 89%